TINJAUAN HUKUM ISLAM TERHADAP URGENSI KURSUS PRA NIKAH TERHADAP KEHARMONISAN RUMAH TANGGA - Andi Muhammad Muammar Qadafi; Hartini Tahir; Muhammad Anis (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem in this research is how to review Islamic law on the urgency of the pre-marital course on household harmony at KUA, Mandai District, Maros Regency. This research was descriptive qualitative research and also field research. The results of this study indicate that the Pre-Marriage Course is very important for every bride and groom before marriage as an effort to create a harmonious family by providing knowledge, understanding, skills and raising awareness to adolescents of marriageable age. Pre-marital courses have urgency because they contain positive values ​​(maṣlahaḥ) and strengthen and support the realization of hifẓ an-nasl. The Pre-Marriage Course is carried out so that the prospective bride and groom can get provisions to build a household and can realize household harmony and avoid divorce. The implication of this research is, it is hoped that every prospective bride and groom will take the Pre-Marriage Course seriously so that the bride and groom can get provisions before starting a family. It is hoped that KUA will continue to provide course materials that support harmony in the household of every bride and groom, Keywords:Islamic Law, Pre-Marriage Course, Household Harmony.